Evaluation of in vitro cytotoxicity of one-dimensional chain [Fe(salen)(L)](n) complexes against human cancer cell lines - Dvořák, Zdeněk; Starha, Pavel; Sindelář, Zdeněk; Trávníček, Zdeněk (Toxicology in vitro, 2012)
The 1d-polymeric iron(III) complexes [Fe(salen)(μ-L)](n) (1-6), involving a deprotonated form of the N-donor heterocyclic compounds (L) imidazole (complex 1), 1,2,4-triazole (2), benztriazole (3), 5-methyltetrazole (4), 5-aminotetrazole (5) and 5-phenyltetrazole (6), were studied for their in vitro cytotoxic activity against human cancer cell lines including lung carcinoma (A549), cervix epithelial carcinoma (HeLa), osteosarcoma (HOS), malignant melanoma (G361), breast adenocarcinoma (MCF7), ovarian carcinoma (A2780) and cisplatin-resistant ovarian carcinoma (A2780cis). Cytotoxicity in vitro (IC50=0.39-0.48 μM) was achieved for 2-6 against A2780 (IC50 of cisplatin equals 11.5 μM) as well as for 5 and 6 against all the tested cells, with IC50=2.5-37.7 μM. The Uv-Vis spectroscopic study showed that the complexes are unstable in organic solvents (e.g., dimethyl sulfoxide, dimethylformamide) containing even trace amounts of water (and thus also in the medium, i.e., 0.1% DMF, v/v, used in the MTT assay), where they partially or completely decompose to the mixtures involving, besides [Fe(salen)(μ-L)](n) itself, also the starting compounds [{Fe(salen)}2(μ-O)] and appropriate organic compound (HL). In efforts to find how the resulting cytotoxicity of the most active compounds 5 and 6 is influenced by this fact, the in vitro cytotoxicity testing of mixtures of reactants [{Fe(salen)}2(μ-O)] and HL, as well as the respective reactants, was also performed. It has been found that the cytotoxicity of 5 and 6 against all the tested cell lines is probably caused by a combined effect of the individual components presented within the corresponding mixture in the medium used.
Keywords: Inhibitory Concentration 50; Drug Stability; Humans; Spectrophotometry, Ultraviolet; Antineoplastic Agents; inhibiční koncentrace 50; Solvents; lidé; Ethylenediamines; rozpouštědla; Ferric Compounds; ethylendiaminy; Neoplasms; železité sloučeniny; nádorové buněčné linie; protinádorové látky; nádory; spektrofotometrie ultrafialová; stabilita léku; Cell Line, Tumor